Emerging drug problems in Asia - Bart, Gavin (2013)
This session, “Emerging Drug Problems in Asia,” focused on emerging drug problems in Asia. Dr. Juana Tomás-Rosselló discussed “East and Southeast Asia: Emerging Drug Problems and Response” and Dr. Wei J. Chen discussed “Ketamine Use among Regular Tobacco and Alcohol Users as Revealed by Respondent Driven Sampling in Taipei: Prevalence, Expectancy, and Users' Risky Decision Making.”